Pengaruh Capital Adequacy Rasio, Dana Pihak Ketiga, dan Non Performing Loan, terhadap Profitabilitas dengan LDR sebagai Variabel Intervening pada Bank Umum Konvensional di Indonesia - Alphamalana, Ivan Lisfi; Paramita, Sista (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Bank is an institution that has a role as a financial intermediary between parties who need funds and can facilitate the payment flows. Additionally, The Bank has a function as industries that rely on public trust, so the health level of the Bank needs to be maintained. Profitability is essential for a bank because it measures a company's effectiveness in generating profits by maximizing its assets. This research aim is to investigate the effect of Capital Adequacy Ratio (CAR), Third Parties Funds (TPF), dan Non-Performing Loan (NPL), on Profitability with LDR as Intervening Variables. This research population is conventional commercial banks in Indonesia between 2012 to 2016. This research type is causality research using quantitative data—the sampling technique using a purposive sampling total of 150 samples. The statistical analysis tool in this research is lane analysis with software versions of AMOS 22 and IBM SPSS. The conclusion from this research results that CAR, TAPI F, and NPL variables affect LDR. The CAR, TPF, and LDR variables have not affected profitability, while the NPL variable affects profitability. Furthermore, CAR, TPF, and NPL cannot mediated by LDR.